2012
DOI: 10.1590/s0103-64402012000300005
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan: effect of a new chelating agent on the microhardness of root dentin

Abstract: The effect of solutions of 0.2% chitosan, 15% EDTA and 10% citric acid on the microhardness of root dentin was evaluated comparatively in this study. Thirteen sound human maxillary central incisors were selected and decoronated at the cementoenamel junction. Ten roots were set into rapid polymerization acrylic resin and the root/resin block was fitted to the cutting machine to obtain slices from the cervical third. The first slice was discarded and the second slice was divided into four quadrants. Each quadran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
2
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 24 publications
4
53
2
13
Order By: Relevance
“…The type of interaction that occurs depends on the involved ions, the chemical structure of chitosan and the pH of the solution (23). Pimenta et al (24) reported that the 0.2% chitosan solution (pH 3.2) has a capacity of reducing dentin microhardness similar to that of 15% EDTA (pH 7.25).…”
Section: Discussionmentioning
confidence: 99%
“…The type of interaction that occurs depends on the involved ions, the chemical structure of chitosan and the pH of the solution (23). Pimenta et al (24) reported that the 0.2% chitosan solution (pH 3.2) has a capacity of reducing dentin microhardness similar to that of 15% EDTA (pH 7.25).…”
Section: Discussionmentioning
confidence: 99%
“…Complexes of chitosan and metal ions are most probably formed by the mechanisms of adsorption, ion exchange and chelation [40,43]. Pimentaet al [44] reported that the 0.2% chitosan solution (pH=3.2) has a capacity to reduce dentin microhardness similar to that of 15% EDTA (pH=7.25) representing similar demineralization potential. The effect of 0.2% chitosan applied for 3 minutes was the most effective for removing the smear layer and smear plug with minimal erosive effect on dentin substrate as suggested previously in the study of Silva et al [38].…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de ambas as substâncias atuarem de formas distintas na quelação do cálcio, pode-se supor, pelos resultados, que a ação de ambas foi equivalente na remoção da lama dentinária, como verificado em outras condições [15][16][17] . A solução de quitosana tem pH mais ácido por ser diluida em ácido acético 1%, e sua ação se baseia em duas teorias: a ligação do grupo amino da cadeia de quitosana se liga ao íon metálico (cálcio), ou seu grupo amino é envolvido na ligação, e por sua vez o íon metálico se ancora ao grupo amino 25 .…”
Section: Methodsunclassified
“…Uma delas é a quitosana, um polissacarídeo natural, abundante na natureza, ecologicamente correto, com propriedades de biocompatibilidade, biodegrabilidade, bioadesão e atoxidade frente ao organismo humano. Tem a capacidade de desmineralizar o tecido dentinário de forma semelhante ao EDTA, proporcionando limpeza das paredes dentinárias por meio da remoção da lama dentinária, com ação equivalente dos ácidos cítrico e diaminotetracético, mas com a vantagem de ser utilizado em pequenas concentrações e por curto período de tempo [14][15][16][17] . Entre as diversas aplicações, a quitosana tem sido utilizada em tratamentos distintos na odontologia, por inibir a formação de biofilmes 18 , pela capacidade de compor scaffolds de alta resistência 19 , por sua ação cicatrizante, anti-inflamatória e antimicrobiana 18,20,21 .…”
Section: Introductionunclassified